Gender comparison of hip muscle activity during single-leg landing - Zazulak, B. T.; Ponce, P. L.; Straub, S. J.; Medvecky, M. J.; Avedisian, L. A.; Hewett, T. E. (Journal of Orthopaedic & Sports Physical Therapy, 2005)
Study Design: Controlled laboratory study. Objectives: To determine whether gender differences in electromyographic (EMG) activity of hip-stabilizing muscles are present during single-leg landing. Background: Numerous factors may explain the greater rate of anterior cruciate ligament (ACL) injuries in female athletes. However, gender differences in hip muscle activity during dynamic events have not been well characterized. Methods and Measures: Twenty-two Division I collegiate athletes (13 female, 9 male) performed drop landings from 30.5- and 45.8-cm heights. Surface EMG was used to examine relative muscle activity from 200 milliseconds prior to initial contact to 250 milliseconds postcontact. Peak and mean values for each muscle (gluteus maximus, gluteus medius, rectus femoris) in each time epoch were analyzed using 2 ×2 (group by height) analyses of variance (ANOVAs) to determine significance. Results: Females demonstrated lower gluteus maximus peak (mean ± SD, 69.5 ± 30.2 versus 98.0 ± 33.4 percent maximum voluntary contraction [%MVIC]; P = .019) and mean (mean ± SD, 37.5 ± 15.6 versus 53.9 ± 18.0 %MVIC; P = .018) muscle activation during the postcontact phase of landing than males. Furthermore, females demonstrated greater peak rectus femoris activity during the precontact phase (mean ± SD, 33.6 ± 18.5 versus 18.7 ± 8.2 %MVIC; P = .029). A positive effect of drop height on relative activity of all muscles was observed during both phases (P<.05). Conclusions: Females utilize different muscular activation patterns compared to males (ie, decreased gluteus maximus and increased rectus femoris muscle activity) during landing maneuvers. Decreased hip muscle activity and increased quadriceps activity may be important contributors to the increased susceptibility of female athletes to noncontact ACL injuries.